KAJIAN HUTAN KEMASYARAKATAN SEBAGAI SUMBER PENDAPATAN : KASUS DI KAB. GUNUNG KIDUL - Raden Mohammad Mulyadin; Surati Surati; Kuncoro Ariawan (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2016)
Community forest (HKm) is a state forest that its utilization specifically for empowering communities around forest areas. Community involvement in forest management is strongly needed to maintain forest sustainability and to achieve community welfare. The study aims to assess activities conducted by the HKm that can be a source of income for forest communities in Gunungkidul district, DI Yogyakarta. Two forest farmer groups (KTH) were chosen as an example of research and as many as 40 farmers as respondents. Collecting data using interview techniques, observation and literature study, was analyzed by using quantitative and descriptive qualitative. The quantitative analysis consisted of household income, balance of receipts and cost analysis. The results showed that HKm activities can increase the income of KTH between 20–50%. Activities that can be used as a source of income consists of the institutional and HKm management intercropped. Intercropping activities by taking into account composition of the main crop in the sidelines of the plant will affect in income levels. The income level of KTH Tani Manunggal greater than KTH Sedyo Lestari, due to differences in the composition between the main crop and plant sidelines, the amount of HKm, and the number of KTH members.